Compressive-decompressive resuscitation with a new device in cardiac patients - Yu. N. Koshelev; V. M. Uskov; V. L. Radushkevich; I. V. Dankov (Российский кардиологический журнал)
The efficacy of compressive-decompressive resuscitation with new device and method in cardiac patients after circulatory arrest was investigated. Comparing to traditional resuscitation methods (Jude J.R., Kouwenhoven W.B., Knickerbocker Y.Y., 1961), efficacy of our original device and methodics was significantly higher. Moreover, it prevented intra-resuscitation traumas of chest osseal components and internal organs.